PENUNDAAN PELAKSANAAN PERJANJIAN ANTARA PENGGUNA JASA DENGAN WEDDING ORGANIZER PADA MASA PANDEMI COVID-19 DI KOTA BENGKULU - Fithriah, Nurhani; Dwi Arso, Dimas; Muljono, Slamet; Edytiawarman, Edytiawarman (UNIB Press, 2023)
ABSTRACT . This study aims to find out and describe the implementation of cooperation between service users and wedding organizers during the Covid-19 period in Bengkulu City. The type of this research is empirical legal research, using qualitative research methods. The results of the study that: (1). The implementation of cooperation between service users and wedding organizers during the Covid-19 period in Bengkulu City had fulfilled the elements of force majeure and the Covid-19 pandemic could be qualified as a force majeure, because when the pandemic hit, the Indonesian Government had declared the Covid-19 pandemic a non-national disaster. natural disasters with the issuance of Presidential Decree Number 12 of 2020 concerning Stipulation of Non-Natural Disasters for the Spread of Coronavirus Disease 2019. Marriage permits in Bengkulu City must comply with health protocols and must have recommendations from the Covid-19 Task Force and fulfill the conditions that have been determined, if these conditions are violated then the Bengkulu City Covid-19 Task Force team will not issue a permit even if it continues it will be disbanded. And if the permit has been issued, it must be postponed due to the emergence of the spread of Covid-19. Therefore, directly making the Focus Wedding Organizer no longer considered a default, but only classified as force majeure. Where the delay in implementing the agreement made the Focus Wedding Organizer and the service user settle each other. (2) Settlement of disputes on service user agreements with Wedding Organizers with AA and NE due to the Covid-19 situation. Done by deliberation and consensus where the aggrieved party finally asks for compensation costs which in this case the amount to be paid each month is IDR 1,645,000 (one million six hundred and forty five thousand rupiah) which is divided into 5 months. Installment payments will be made every 20th starting from November and 2020 ending in April 2021. Keywords: Agreement, Settlement, Breach of Contract.